Type I IFN signaling blockade by a PASylated antagonist during chronic SIV infection suppresses specific inflammatory pathways but does not alter T cell activation or virus replication - Nganou-Makamdop, Krystelle; Billingsley, James M.; Yaffe, Zachary; O’Connor, Gregory; Tharp, Gregory K.; Ransier, Amy; Laboune, Farida; Matus-Nicodemos, Rodrigo; Lerner, Andrea; Gharu, Lavina; Robertson, Jennifer M.; Ford, Mandy L.; et al. (PLoS pathogens, 2018)
Chronic activation of the immune system in HIV infection is one of the strongest predictors of morbidity and mortality. As such, approaches that reduce immune activation have received considerable interest. Previously, we demonstrated that administration of a type I interferon receptor antagonist (IFN-1ant) during acute SIV infection of rhesus macaques results in increased virus replication and accelerated disease progression. Here, we administered a long half-life PASylated IFN-1ant to ART-treated and ART-naïve macaques during chronic SIV infection and measured expression of interferon stimulated genes (ISG) by RNA sequencing, plasma viremia, plasma cytokines, T cell activation and exhaustion as well as cell-associated virus in CD4 T cell subsets sorted from peripheral blood and lymph nodes. Our study shows that IFN-1ant administration in both ART-suppressed and ART-untreated chronically SIV-infected animals successfully results in reduction of IFN-I-mediated inflammation as defined by reduced expression of ISGs but had no effect on plasma levels of IL-1β, IL-1ra, IL-6 and IL-8. Unlike in acute SIV infection, we observed no significant increase in plasma viremia up to 25 weeks after IFN-1ant administration or up to 15 weeks after ART interruption. Likewise, cell-associated virus measured by SIV gag DNA copies was similar between IFN-1ant and placebo groups. In addition, evaluation of T cell activation and exhaustion by surface expression of CD38, HLA-DR, Ki67, LAG-3, PD-1 and TIGIT, as well as transcriptome analysis showed no effect of IFN-I blockade. Thus, our data show that blocking IFN-I signaling during chronic SIV infection suppresses IFN-I-related inflammatory pathways without increasing virus replication, and thus may constitute a safe therapeutic intervention in chronic HIV infection.